Let x 0 , x 1 , x 2 , … be a sequence of a numbers satisfying the recursion,
x n = 2 x n − 1 + x n + 1 ,
for n = 1 , 2 , 3 , … .
Given that x 3 4 3 4 3 4 and x 5 1 5 1 5 1 are non-negative real numbers whose sum is 5 , find the number of possible integral values of x 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice approach!
The first recursion relation implies an arithmetic progression.
So, x 0 has the range from − 1 0 to 1 5 .
So it has 2 6 possible integral values.
Although @Pi Han Goh pointed out that this solution is a little unsatisfying and somewhat incomplete. Can anyone think of a more straightforward way to explain the solution?
Perhaps it helps to consider that the numbers 3 4 3 4 3 4 and 5 1 5 1 5 1 have little relevance other than that 3 4 3 4 3 4 is 3 2 of 5 1 5 1 5 1 . So, the problem is essentially the same as if you said x 2 and x 3 , a much simpler problem to visualize/solve.
The way that I would phrase it is:
x
0
+
2
x
5
1
5
1
5
1
=
3
x
3
4
3
4
3
4
by properties of arithmetic progressions. (You can show it via the
a
+
(
n
−
1
)
d
substitution.)
Hence,
x
0
=
3
x
3
4
3
4
3
4
−
2
x
5
1
5
1
5
1
=
1
5
−
5
x
5
1
5
1
5
1
.
Since
0
≤
x
5
1
5
1
5
1
≤
5
, it follows that
1
5
≥
x
0
≥
−
1
0
, and so there are 26 possible values for
x
0
.
Log in to reply
Ah yes... That's the verbiage I was looking for! :)
oh my god, i forgot about zero, damn it !! i was going mad why 25 is wrong , i would have had been level 5 in algebra.
x n 2 x n x n + x n x n − x n − 1 = 2 x n − 1 + x n + 1 = x n − 1 + x n + 1 = x n − 1 + x n + 1 = x n + 1 − x n
Let x n − x n − 1 = x n + 1 − x n = k , then x n − 1 = x n − k and x n + 1 = x n + k
x n − 1 , x n , x n + 1 ⇔ x n − k , x n , x n + k (it shows us that x n follow aritmetical progression)
Then, we can get that x n = x 0 + n k
n = 3 4 3 4 3 4 ⟹ x 3 4 3 4 3 4 = x 0 + 3 4 3 4 3 4 k
n = 5 1 5 1 5 1 ⟹ x 5 1 5 1 5 1 = x 0 + 5 1 5 1 5 1 k
x 3 4 3 4 3 4 + x 5 1 5 1 5 1 5 5 5 − 2 x 0 k = ( x 0 + 3 4 3 4 3 4 k ) + ( x 0 + 5 1 5 1 5 1 k ) = x 0 + 3 4 3 4 3 4 k + x 0 + 5 1 5 1 5 1 k = 2 x 0 + 8 5 8 5 8 5 k = 8 5 8 5 8 5 k = 8 5 8 5 8 5 5 − 2 x 0
x 3 4 3 4 3 4 x 0 + 3 4 3 4 3 4 k x 0 + 3 4 3 4 3 4 × 8 5 8 5 8 5 5 − 2 x 0 x 0 + 5 2 ( 5 − 2 x 0 ) x 0 + 2 − 5 4 x 0 5 1 x 0 x 0 ≥ 0 ≥ 0 ≥ 0 ≥ 0 ≥ 0 ≥ − 2 ≥ − 1 0
x 5 1 5 1 5 1 x 0 + 5 1 5 1 5 1 k x 0 + 5 1 5 1 5 1 × 8 5 8 5 8 5 5 − 2 x 0 x 0 + 5 3 ( 5 − 2 x 0 ) x 0 + 3 − 5 6 x 0 3 1 5 x 0 ≥ 0 ≥ 0 ≥ 0 ≥ 0 ≥ 0 ≥ 5 1 x 0 ≥ x 0 ≤ 1 5
⟹ − 1 0 ≤ x 0 ≤ 1 5
So, the number possible integral values of x 0 is 2 6
Nice write up, James! (cc'ing @Pi Han Goh who will likely be interested)
Log in to reply
Thanks Sir @Geoff Pilling, it's a nice question too, I like it!
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Induction - Recurrence Relations
The recursion relation implies that x n is an arithmetic progression. I choose not to use this fact but go for a more elementary approach:
Lemma : 2 x n = x n − a + x n + a .
Proof by induction on a . The case a = 0 is trivial, and a = 1 is the given recursion relation. Now assume the relation is true up to some value of a ≥ 1 . Then x n − ( a + 1 ) + x n + ( a + 1 ) = 2 x n − a − x n − ( a − 1 ) + 2 x n + a − x n + ( a − 1 ) = 2 ( x n − a + x n + a ) − ( x n − ( a − 1 ) + x n + ( a − 1 ) ) = 4 x n − 2 x n = 2 x n , Q.E.D.
Taking n = 3 4 3 4 3 4 and a = 1 7 1 7 1 7 we conclude that x 1 7 1 7 1 7 + x 5 1 5 1 5 1 = 2 x 3 4 3 4 3 4 ∴ x 1 7 1 7 1 7 = 2 x 3 4 3 4 3 4 − x 5 1 5 1 5 1 ; similarly, x 0 + x 3 4 3 4 3 4 = 2 x 1 7 1 7 1 7 ∴ x 0 = 2 x 1 7 1 7 1 7 − x 3 4 3 4 3 4 = 3 x 3 4 3 4 3 4 − 2 x 5 1 5 1 5 1 , and since x 3 4 3 4 3 4 + x 5 1 5 1 5 1 = 5 , we can write this as x 0 = 5 x 3 4 3 4 3 4 − 1 0 or x 0 = 1 5 − 5 x 5 1 5 1 5 1 . Since x 3 4 3 4 3 4 ≥ 0 we have x 0 ≥ − 1 0 ; since x 5 1 5 1 5 1 ≥ 0 we have x 0 ≤ 1 5 .
Thus x 0 can take all integer values in the range x 0 ∈ { − 1 0 , − 9 , … , 1 4 , 1 5 } , showing that there are 1 5 − ( − 1 0 ) + 1 = 2 6 possible values for x 0 .